Supplementary benefits of CT-guided transthoracic lung aspiration biopsy for core needle biopsy - He, Jia-Huan; Ruan, Jia-Xing; Lei, Ying; Hua, Zhi-Dan; Chen, Xiang; Huang, Da; Chen, Cheng-Shui; Jin, Xu-Ru (Frontiers in Microbiology, 2022)
Objective This study aimed to investigate the diagnostic efficacy of computed tomography (CT)-guided transthoracic lung core needle biopsy combined with aspiration biopsy and the clinical value of this combined routine microbial detection. Materials and methods We retrospectively collected the electronic medical records, CT images, pathology, and other data of 1085 patients with sequential core needle biopsy and aspiration biopsy of the same lung lesion under CT guidance in the First Affiliated Hospital of Wenzhou Medical University from January 2016 to January 2021. GenXpert MTB/RIF detection and BD BACTEC™ Mycobacterium/fungus culture were applied to identifying the microbiological results of these patients. We then compared the positive diagnostic rate, false negative rate, and diagnostic sensitivity rate of three methods including core needle biopsy alone, aspiration biopsy alone, and both core needle biopsy and aspiration biopsy. Results The pathological results of cutting histopathology and aspiration of cell wax were examined for 1085 patients. The diagnostic rates of cutting and aspiration pathology were 90.1% (978/1085) and 86.3% (937/1085), respectively, with no significant difference (P > 0.05). Considering both cutting and aspiration pathologies, the diagnostic rate was significantly improved, up to 98% (1063/1085) (P < 0.001). A total of 803 malignant lesions were finally diagnosed (803/1085, 74.0%). The false negative rate by cutting pathology was 11.8% (95/803), which was significantly lower than that by aspiration biopsy [31.1% (250/803), P < 0.001]. Compared with core needle biopsy alone, the false negative rate of malignant lesions decreased to 5.6% (45/803) (P < 0.05). Next, the aspirates of the malignant lesions highly suspected of corresponding infection were cultured. The results showed that 16 cases (3.1%, 16/511) were infected with Mycobacterium tuberculosis complex, Aspergillus niger, and Acinetobacter baumannii, which required clinical treatment. 803 malignant tumors were excluded and 282 cases of benign lesions were diagnosed, including 232 cases of infectious lesions (82.3%, 232/282). The diagnostic rate of Mycobacterium/fungus culture for infectious lesions by aspiration biopsy (47.4%) was significantly higher than that by lung core needle biopsy (22.8%; P < 0.001). The diagnostic rate of aspiration biopsy combined with core needle biopsy was 56% (130/232). The parallel diagnostic rate of aspirated biopsy for GenXpert detection and Mycobacterium/fungal culture combined with core needle biopsy was 64.7% (150/232), which was significantly higher than that of lung core needle biopsy alone (P < 0.001). Finally, pulmonary tuberculosis was diagnosed in 90 cases (38.8%) of infectious lesions. Compared with the sensitivity of core needle biopsy to detect tuberculosis (27.8%, 25/90), the sensitivity of aspirating biopsy for GenXpert detection and Mycobacterium/fungal culture was significantly higher, at 70% (63/90) and 56.7% (51/90), respectively. Although there was no significant difference in the sensitivity of aspirated biopsy for GenXpert and Mycobacterium/fungal culture to detect pulmonary tuberculosis, the sensitivity was significantly increased to 83.3% (P < 0.05) when the two tests were combined. Moreover, when aspirated biopsies were combined with GenXpert detection, Mycobacterium/fungus culture, and core needle biopsy, the sensitivity was as high as 90% (81/90). Conclusion CT-guided lung aspiration biopsy has a significant supplementary effect on core needle biopsies, which is indispensable in clinical application. Additionally, the combination of aspiration biopsy and core needle biopsy can significantly improve the diagnostic rate of benign and malignant lesions. Aspiration biopsy showed that pulmonary malignant lesions are complicated with pulmonary tuberculosis, aspergillus, and other infections. Finally, the diagnostic ability of lung puncture core needle biopsy and aspiration biopsy combined with routine microbial detection under CT positioning in the diagnosis of pulmonary infectious diseases was significantly improved.